Ultrasound-guided needle aspiration of amoebic liver abscess. Issue 811 (May 1993) - Ramani, A.; Ramani, R.; Kumar, M. S.; Lakhkar, B. N.; Kundaje, G. N.
Abstract : This prospective study was carried out on 200 patients with clinically, ultrasonographically and serologically confirmed amoebic liver abscess. The role of ultrasound-guided needle aspiration in addition to medications was evaluated compared to drug treatment alone. Both the groups were monitored clinically and sonographically for up to 6 months after diagnosis. The initial response (after 15 days) was better in the aspirated group (P < 0.05) but resolution of abscess after 6 months were similar. There was a more rapid clinical response in the aspirated group, particularly in those with larger (> 6 cm) abscesses and there were no complications. Percutaneous ultrasound-guided needle aspiration is a safe diagnostic and therapeutic approach which enhances clinical recovery, accelerates resolution, especially in large abscesses, and prevents complications.